2020
DOI: 10.1016/j.heliyon.2020.e04834
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable reverse logistics scorecards for the performance measurement of informal e-waste businesses

Abstract: Many countries depend on businesses in reverse chains to tackle the environmental pollution caused by the tremendous amount of e-waste. Furthermore, due to the domination of informal businesses in many developing countries, environmental rules are not considered during operation, and these violations tend to affect public health adversely. The government in these developing countries finds it difficult to manage and utilize e-waste due to insufficient resources properly. The existing performance measures are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Therefore, several objectives may be accomplished by an organization with an efficient RL management system, including enhancing the total value of the brand, cutting operating expenses, complying with environmental norms, and improving customer satisfaction. In support of this claim, Maheswari, Yudoko, Adhiutama, and Agustina [10] argue that RL enables businesses to better manage waste and become more competitive as a result of their increased environmental efficiency. Bajar, Kamat, Shanker, and Barve [11] found that RL may help businesses in a number of ways, including attracting new clients, cutting expenses, enhancing operations, and boosting public perception.…”
Section: Fast Moving Consumer Goods (Fmcgs) and Suppliers In South Af...mentioning
confidence: 99%
“…Therefore, several objectives may be accomplished by an organization with an efficient RL management system, including enhancing the total value of the brand, cutting operating expenses, complying with environmental norms, and improving customer satisfaction. In support of this claim, Maheswari, Yudoko, Adhiutama, and Agustina [10] argue that RL enables businesses to better manage waste and become more competitive as a result of their increased environmental efficiency. Bajar, Kamat, Shanker, and Barve [11] found that RL may help businesses in a number of ways, including attracting new clients, cutting expenses, enhancing operations, and boosting public perception.…”
Section: Fast Moving Consumer Goods (Fmcgs) and Suppliers In South Af...mentioning
confidence: 99%
“…It is a method that allows a producer to efficiently recognize previously shipped things from the point of use for possible reuse, remanufacturing, or disposal. The reverse logistics framework combines a renewed supply chain to handle a flow of things or parts destined for remanufacturing, reuse, or transfer, as well as to effectively utilize resources (Maheswari et al, 2020; Dowlatshahi, 2000). Emerging economies are more likely than industrialized ones to destroy or burn usable and valued items and products.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…16,17,40 Using RL methods to reduce costs is an essential strategy in a highly commoditized sector where repurchase behavior is influenced by price. 41 According to Maheswari et al 25 , reduced material and power costs, as well as lower expenditures for environmental issues, are all examples of cost savings that may be attained with RL practices. Furthermore, organizations have the chance to boost their revenue by recovering the value of returned goods through reuse and recycling.…”
Section: Drivers Of the Implementation Of Rlmentioning
confidence: 99%